STUDY OF NUTRIENT CONTENT IN ECO ENZYMES FROM VARIOUS TYPES OF ORGANIC MATERIALS - Panataria, Lince Romauli; Sianipar, Ebsan; Sembiring, Harianda; Sitorus, Efbertias; Saragih, Meylin; Simatupang, Jones; Pakpahan, Helena (Journal of Agriculture, 2022)
One of the organic waste processing technologies is Eco Enzyme. Eco enzyme is a complex solution of light to dark brown color, which has a fresh sour aroma. Organic waste, in the form of fruit peels, unused fruit flesh, and vegetable pieces, is collected in containers/barrels and then mixed with molasses/brown sugar and water with a certain dose. The recommended dose for the ratio of molasses: organic waste: water is 1:3:10. The fermentation results produce environmentally friendly enzymes and other beneficial elements for agriculture. This study aims to determine the nutrient content of P2O5, K2O, and the C/N ratio of eco enzymes derived from various organic materials. This study used a non-factorial, completely randomized design (CRD). This study used 6 treatment combinations consisting of: P1 = Musa paradisiaca L Boobs (1.5 kg) + Tithonia diversifolia Leaves (1.5 kg); P2 = Musa paradisiaca L weevil (1.5 kg) + Terminalia catappa leaves (1.5 kg); P3= Musa paradisiaca L Weevil (1.5 kg) + Spreading Leaf Shoots (1.5 kg); P4= Mimosa pudica Root (1.5 kg) + Tithonia diversifolia Leaf (1.5 kg); P5 = roots of Mimosa pudica daughter (1.5 kg) + Terminalia catappa leaves (1.5 kg); P6 = Roots of Mimosa pudica (1.5 kg) + Shoots of Spreading Leaves (1.5 kg). The results showed that using organic materials significantly affected the K2O content and the C/N ratio of the eco enzyme.